2019
DOI: 10.1021/acs.energyfuels.9b01217
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Environmentally Friendly and Interfacially Active CNTs/SiO2 Demulsifier for W/O Crude Oil Emulsion Separation

Abstract: In the current study, novel environmentally friendly and interfacially active carbon nanotubes/SiO 2 nanomaterials (CNTs/SiO 2 ) for emulsified crude oil separation were prepared via grafting nano-SiO 2 on the surface of oxidized carbon nanotubes (Ox-CNTs). The structure of the as-prepared CNTs/SiO 2 was characterized by Fourier transform infrared spectroscopy, UV−visible absorption spectra, Raman spectra, X-ray diffraction spectra, thermogravimetric analysis, field-emission scanning electron microscope, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…The weight loss of the sample in the 30–200 °C range was 7.44 % and is ascribed to the large amounts of amino groups in the molecular structure of the PPDA demulsifier . The amino group is a hydrophilic group that will combine with the water molecules in the air . In the heating process, the water molecules attached to the amine groups will be broken up, resulting in a weight loss due to the evaporation of water.…”
Section: Resultsmentioning
confidence: 99%
“…The weight loss of the sample in the 30–200 °C range was 7.44 % and is ascribed to the large amounts of amino groups in the molecular structure of the PPDA demulsifier . The amino group is a hydrophilic group that will combine with the water molecules in the air . In the heating process, the water molecules attached to the amine groups will be broken up, resulting in a weight loss due to the evaporation of water.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the distribution of nanomaterials at the interfaces has improved the coalescence of water droplets, which quickly and effectively separated water from crude oil emulsions. 134…”
Section: Crude Oil Demulsification Usingmentioning
confidence: 99%
“…Figure 9. Effect of different concentrations and sedimentation times of CNTs/SiO 2 on demulsification efficiency 134. …”
mentioning
confidence: 99%
“…Therefore, demulsification and removal of water from crude oil are of great significance. At present, demulsification methods include centrifugation, microwave and heat treatment, membrane separation, flocculation, chemical demulsification, biological technology, and so on [8–14] . At present, chemical demulsification is the most commonly used demulsification method [15–17] .…”
Section: Introductionmentioning
confidence: 99%
“…At present, demulsification methods include centrifugation, microwave and heat treatment, membrane separation, flocculation, chemical demulsification, biological technology, and so on. [8][9][10][11][12][13][14] At present, chemical demulsification is the most commonly used demulsification method. [15][16][17] The chemical demulsifier is a kind of surfactant.…”
Section: Introductionmentioning
confidence: 99%